A Study of Compressive Strength and Density of Aerated Concrete - Kraiwood Kiattikomol; Aikachai Sae Lim; Anek Siripanichgorn (ASEAN Journal on Science and Technology for Development, 1988)
A Study of Compressive Strength and Density of Aerated Concrete